2020
DOI: 10.1038/s41433-020-01234-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous incarceration in sutured vs non-sutured sclerotomies after 25-gauge macular surgery

Abstract: Objectives To study the patterns of vitreous incarceration in sutured vs non-sutured sclerotomies in patients subjected to 25gauge macular surgery. Methods A prospective study of 135 eyes affected by epiretinal membrane or macular hole. Vitreal disposition was evaluated via ultrasound biomicroscopy (UBM) at the sclerotomy sites between 30 and 40 days after surgery, once the tamponade had completely disappeared. Results In total, 349 sclerotomies (86.2%) of 99 patients were non-sutured while 56 sclerotomies (13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…However, they also found that suturing the sclerotomy was significantly associated with a less pronounced form of vitreous incarceration. 15 Longitudinal analysis of the vitreous base after vitrectomy surgery may be useful in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also found that suturing the sclerotomy was significantly associated with a less pronounced form of vitreous incarceration. 15 Longitudinal analysis of the vitreous base after vitrectomy surgery may be useful in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It results in post-operative hypotony and further complications like endophthalmitis. 7,8 Different techniques have been adapted to address the sclerotomy leak. 9,10 Some of the techniques include suturing of sclerotomy with vicryl8-0, nylon8-0 and plain gut 6 -0 suture.…”
Section: Introductionmentioning
confidence: 99%
“…These include bipolar diathermy, tissue adhesives and releasable sutures. 9 The standard practice at our hospital is to apply sutures with 23G PPV. In this study, we performed PPV without sutures and investigated the prognosis in such cases.…”
Section: Introductionmentioning
confidence: 99%